2014
DOI: 10.1111/trf.12897
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin–associated thrombosis: is it such a rare event? Report of a pediatric case and of the Quebec Hemovigilance System

Abstract: Thrombosis after IVIG is a rare though SAE occurring mostly in adults. This underlines the importance of properly reporting IVIG SAEs to improve hemovigilance data and study such rare events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…One patient presented cerebral thrombophlebitis after IVIg, which was extended after another IVIg infusion despite AC treatment, with a fatal result. Thrombotic events after IVIg are rare in large databases, but our findings and some previous reports, sometimes with death, suggest that physicians should be vigilant regarding the possibility of thrombotic complications with IVIg infusion, particularly in patients with a past history of a VTE.…”
Section: Discussionmentioning
confidence: 46%
“…One patient presented cerebral thrombophlebitis after IVIg, which was extended after another IVIg infusion despite AC treatment, with a fatal result. Thrombotic events after IVIg are rare in large databases, but our findings and some previous reports, sometimes with death, suggest that physicians should be vigilant regarding the possibility of thrombotic complications with IVIg infusion, particularly in patients with a past history of a VTE.…”
Section: Discussionmentioning
confidence: 46%
“…Meta‐analysis of three studies revealed an increased rate of VOD in recipients receiving IVIG. Thromboembolic events have been reported to be associated with IVIG presumably due to a hypercoagulable state, although a recent meta‐analysis did not confirm such an association . Thrombotic events are usually associated with high doses and rapid administration of IVIG .…”
Section: Discussionmentioning
confidence: 99%
“…The main findings in the literature on this topic are shown in ►Table 1. [64][65][66][67][68][69][70][71][72][73][74] Despite the inconclusive evidence, in 2002 the U.S. Food and Drug Administration required an updated package labeling for Ig to include a warning about the risk of thrombotic events. 75 Taking into account these limitations, the reported incidence of thrombotic events varies from 3 to 13%.…”
Section: Intravenous Immunoglobulinsmentioning
confidence: 99%
“…Thus, in this population, thrombosis was not a frequent complication of IVIg therapy. 74 IVIg are sometimes used in SLE and in antiphospholipid syndrome (APS) treatment. APS is a condition in which the presence of antiphospholipid antibodies is related to development of arterial and venous thromboses, and it may affect subjects with or without other autoimmune disease, particularly SLE.…”
Section: Intravenous Immunoglobulinsmentioning
confidence: 99%